Ceredrovascular impedance measurements with US Doppler technique - ALVISI, Carlo; GIULIONI, Marco; CERISOLI, Marziano; GIULIANI, Giuliano; MONARI, Paolo; PALLOTTI, Clemente (Archives of Acoustics, 1984)
The Authors present different experimental models performed in the attempt to determine whether the alterations of brain circulation following an increase in the intracranial impedance can be estimated by systolic and diastolic common carotid artery (CCA) velocity Doppler signals recorded at 15-minute intervals until 60 minutes and 10 hours. In model 1 both jugular veins (JV) were ligated and Doppler signals were recorded at 15-minute intervals until 60 minutes. In model 2 ipsilateral external carotid artery (ECA) ligation was added to JV occlusion. In model 3 recording of Doppler signals was performed at 15-minute intervals until 60 minutes and 10 hours in the presence of ipsilateral ECA and bilateral JV occlusion. In model 4 Doppler signals were recorded in the presence of ipsilateral ECA occlusion alone.Statistically significant results confirming the well-known theoretical relationship between increased encephalic impedance and flow velocity Doppler signals were obtained in model 3. The results demonstrated that a sudden increase in the encephalic impedance can affect both systolic and diastolic flow velocities in afferent vessels.Later (from 60 minutes to 10 hours), systolic values tend to increase and at 10 hours are always higher than starting values. The diastolic values, however, remain inferior to the starting values, although showing a slight tendency to rise.The Authors conclude that significative alterations of cerebrovascular impedance can be obtained by clamping both JV. However, these alterations can be recorded on the CCA only if the ipsilateral ECA is occluded, thus eliminating the risk of run-off across it, or if recordings are taken from the internal carotid artery.